PELAKSANAAN REKRUTMEN CPNS DI LINGKUNGAN BAWASLU RI PADA TAHUN 2021 BERDASARKAN UNDANG-UNDANG NOMOR.5 TAHUN 2014 TENTANG APARATUR SIPIL NEGARA: Implementation of the Recruitment of the of Civil Servant Candidates in Bawaslu RI in 2021 Based on Law Number 5 of 2014 Concerning the State Civil Apparatus - Ananda Alfiyah Jasmine Siagian Siregar; Yogo Pamungkas (Universitas Trisakti, 2024)
Abstract A democratic, innovative and transparent government system has always been the hope for society and government in this modern era. One element of government that must be considered in order to realize this, one of which is through the arrangement of Human Resources (HR) within each agency or institution. Law Number 5 of 2014 concerning ASN and with internal regulations in the RI Bawaslu is a guideline for BAWASLU in carrying out recruitment of ASN employees in the BAWASLU environment for the 2021 fiscal year. The main problems of this thesis are 1) How is the selection (recruitment) of CPNS at RI Bawaslu environment in 2021? 2) Is the implementation of CPNS recruitment in the RI Bawaslu environment in accordance with Law Number 5 of 2014?. This thesis is a normative legal research that is descriptive in nature, with literature studies and interviews as well as deductive conclusions. The secondary data obtained was processed qualitatively. The results of the research show that: 1) The author describes the flow of the recruitment process in the RI Bawaslu Environment based on related regulations. 2) The author found negligence and violations that had been committed by unscrupulous CPNS selection teams in the Bawaslu environment in 2021 which were not in accordance with Law no. 5 of 2014 concerning the State Civil Apparatus. Keywords: State Civil Apparatus (ASN); Indonesian Bawaslu; Recruitment